Cursed Britain : a history of witchcraft and black magic in modern times - Waters, Thomas E., 1983- (Yale University Press, 2019)
The definitive history of how witchcraft and black magic have survived, through the modern era and into the present dayCursed Britain unveils the enduring power of witchcraft, curses and black magic in modern times. Few topics are so secretive or controversial. Yet, whether in the 1800s or the early 2000s, when disasters struck or personal misfortunes mounted, many Britons found themselves believing in things they had previously dismissed - dark supernatural forces. Historian Thomas Waters here explores the lives of cursed or bewitched people, along with the witches and witch-busters who helped and harmed them. Waters takes us on a fascinating journey from Scottish islands to the folklore-rich West Country, from the immense territories of the British Empire to metropolitan London. We learn why magic caters to deep-seated human needs but see how it can also be abused, and discover how witchcraft survives by evolving and changing. Along the way, we examine an array of remarkable beliefs and rituals, from traditional folk magic to diverse spiritualities originating in Africa and Asia. This is a tale of cynical quacks and sincere magical healers, depressed people and furious vigilantes, innocent victims and rogues who claimed to possess evil abilities. Their spellbinding stories raise important questions about the state's role in regulating radical spiritualities, the fragility of secularism and the true nature of magic.